Positive electrode active material and lithium secondary battery including the same

By forming a coating of fluorine and boron on the surface of lithium manganese-based oxides, the disadvantages of lithium manganese-based oxides in electrochemical performance and stability in lithium secondary batteries are solved, and higher discharge capacity, better rate performance and longer service life are achieved.

CN119786547APending Publication Date: 2025-04-08ECOPRO BM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411227888.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-06
Filing Date
2024-09-03
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing lithium-rich lithium manganese-based oxides have disadvantages in electrochemical performance and stability in lithium secondary batteries, especially in terms of rate performance and capacity retention.

Method used

The electrochemical properties and stability of the lithium manganese-based oxide are improved by forming a coating containing fluorine and boron on the surface of the lithium manganese-based oxide. By controlling the content of fluorine and boron, the coating can inhibit the dissolution of the transition metal and the side reaction between the electrolyte and the positive electrode active material.

Benefits of technology

The discharge capacity, charging/discharge efficiency and rate performance of lithium manganese-based oxides are improved, the service life of lithium secondary batteries is extended, and the high-temperature characteristics and stability of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005025198880000291
    Figure BDA0005025198880000291
  • Figure BDA0005025198880000301
    Figure BDA0005025198880000301
Patent Text Reader

Abstract

The present invention relates to a positive electrode active material and a lithium secondary battery including the same. More specifically, the present invention relates to a positive electrode active material and a lithium secondary battery including the same. The positive electrode active material is a positive electrode active material including a lithium-rich lithium manganese-based oxide, which can improve the electrochemical properties of the lithium secondary battery including discharge capacity, rate performance, etc., which are reduced due to excessive lithium and manganese in the lithium manganese-based oxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a positive electrode active material and a lithium secondary battery including the same. More specifically, the present invention relates to a positive electrode active material and a lithium secondary battery including the same. The positive electrode active material is a positive electrode active material including a lithium-rich lithium manganese-based oxide, which can improve the electrochemical properties of the lithium secondary battery including discharge capacity, rate performance, etc., which are reduced due to excessive lithium and manganese in the lithium manganese-based oxide. Background Art

[0002] Batteries use materials that can undergo electrochemical reactions at the positive and negative electrodes to store electrical energy. A typical example of such batteries is a lithium secondary battery that stores electrical energy through the chemical potential difference when lithium ions are inserted / released between the positive and negative electrodes.

[0003] The lithium secondary battery is prepared by using a substance capable of reversibly inserting and extracting lithium ions as a positive electrode active material and a negative electrode active material, and filling an organic electrolyte or a polymer electrolyte between the positive electrode and the negative electrode.

[0004] Representative materials used as positive electrode active materials for lithium secondary batteries include lithium composite oxides. Examples of the lithium composite oxides include LiCoO2, LiMn2O4, LiNiO2, LiMnO2, or complex oxides of nickel, cobalt, manganese, or aluminum.

[0005] Among the above-mentioned positive electrode active materials, LiCoO2 is the most widely used due to its excellent life characteristics and charge and discharge efficiency, but its price competitiveness is limited due to the resource limitation of cobalt used as a raw material and its high price.

[0006] Lithium manganese-based oxides such as LiMnO2 and LiMn2O4 have the advantages of excellent thermal stability and low price, but have problems of small capacity and poor high temperature characteristics. In addition, LiNiO2-based positive electrode active materials have battery characteristics of high discharge capacity, but due to the cation mixing problem between lithium and transition metals, they are difficult to synthesize, resulting in major problems in rate performance.

[0007] Furthermore, depending on the severity of such cation mixing, a large amount of lithium byproducts are generated, most of which are composed of compounds of LiOH and Li2CO3, so when preparing the positive electrode slurry, it leads to gelation, or after preparing the electrode, it may become a cause of gas generation due to repeated charge and discharge. In addition, the residual Li2CO3 in the above lithium byproducts increases the swelling phenomenon of the monomer and becomes a cause of reducing the service life.

[0008] Various candidate materials are being discussed for compensating for the shortcomings of these existing positive electrode active materials.

[0009] For example, research is underway to use lithium-rich manganese-based oxides containing excess manganese in transition metals and a lithium content greater than the total content of transition metals as positive electrode active materials for lithium secondary batteries. Such lithium-rich manganese-based oxides are also called overlithi ated layered oxides (OLO).

[0010] Although the above OLO has the advantage of showing high capacity under high voltage working environment in theory, in reality, due to the excessive manganese contained in the oxide, its conductivity is relatively low, so there is a disadvantage that the rate performance of the lithium secondary battery using OLO is low. As mentioned above, when the rate performance is low, the charge / discharge capacity and life efficiency (cycle capacity retention) deteriorate during the cycle of the lithium secondary battery.

[0011] In order to solve the above problems, research has been conducted to change the composition of OLO, but these attempts have not yet reached commercialization level. Summary of the invention

[0012] Technical issues

[0013] In the lithium secondary battery market, the growth of lithium secondary batteries for electric vehicles plays a leading role in the market, and the demand for positive electrode active materials used in lithium secondary batteries is also constantly changing.

[0014] For example, in the related art, lithium secondary batteries using lithium iron phosphate (LFP) are mainly used from the viewpoint of ensuring safety, etc., but recently, the use of nickel-based lithium composite oxides having a large energy capacity per unit weight compared with LFP has been expanded.

[0015] In addition, nickel-based lithium composite oxides, which are mainly used as positive electrode active materials for high-capacity lithium secondary batteries in recent years, must use ternary metal elements such as nickel, cobalt and manganese or nickel, cobalt and aluminum. However, since cobalt is not only unstable in supply and demand but also too expensive compared to other raw materials, a positive electrode active material with a new composition that can reduce the cobalt content or does not contain cobalt is needed.

[0016] Taking the whole situation into consideration, although lithium-rich lithium manganese-based oxides can meet the expectations of the above-mentioned market, the above-mentioned lithium manganese-based oxides still have limitations in replacing commercial positive electrode active materials such as ternary lithium composite oxides composed of nickel cobalt manganese (NCM) or nickel cobalt aluminum (NCA), especially the lack of electrochemical performance.

[0017] On the other hand, the inventors of the present invention have confirmed that lithium manganese-based oxides are more likely to have transition metals eluted from the particle surface during repeated charge and discharge than ternary lithium composite oxides. In particular, manganese contained in excess in lithium manganese-based oxides is more likely to be eluted from the particle surface.

[0018] When the transition metal is eluted from the lithium manganese-based oxide, the eluted transition metal may react with the electrolyte on the surface of the lithium manganese-based oxide to form impurities. The impurities not only increase the surface resistance of the lithium manganese-based oxide, but also become the cause of reducing the insertion / extraction efficiency of lithium ions through the lithium manganese-based oxide.

[0019] Furthermore, transition metals dissolved from the above-mentioned lithium manganese-based oxide or impurities formed by the reaction of the dissolved transition metals with the electrolyte may move to the negative electrode through the electrolyte as a medium and may be deposited on the surface of the negative electrode.

[0020] For example, due to a side reaction between the surface of the lithium manganese-based oxide and the electrolyte or a structural change (crystal structure change, etc.) of the lithium manganese-based oxide, the excessive amount of Mn contained in the lithium manganese-based oxide may be 2+ Mn dissolved in the electrolyte may be dissolved in the electrolyte. 2+ During the formation or charge-discharge process, the electrolyte may move to the negative electrode surface, thereby reacting with various substances (electrons, electrolyte, electrodes or by-products, etc.) present in the battery. As a result, Mn 2+ , Mn metal or Mn-containing compounds (e.g., MnCO3, MnO, MnF2, etc.) impurities exist.

[0021] Transition metals or impurities deposited on the surface of the negative electrode will rapidly increase the resistance of the negative electrode. This resistance anomaly is a representative cause of accelerated deterioration of the life of lithium secondary batteries.

[0022] In particular, in the case of a lithium secondary battery using the above-mentioned lithium manganese-based oxide as a positive electrode active material, the operating voltage is higher than that of a lithium secondary battery using other commercially available ternary lithium composite oxides as a positive electrode active material, so the above-mentioned problem is likely to occur.

[0023] However, there is currently no technology for addressing the dissolution of transition metals from lithium-rich lithium manganese-based oxides and the problems arising therefrom.

[0024] As described above, compared with other types of commercially available positive electrode active materials, existing lithium-rich lithium manganese-based oxides have disadvantages in electrochemical performance and / or stability. However, the present inventors have confirmed that when a coating (e.g., a boron-containing coating) of a specific composition is formed on the surface of the lithium manganese-based oxide, the dissolution of transition metals from the surface of the lithium manganese-based oxide can be suppressed or reduced.

[0025] However, as described above, when a coating of a specific composition of the above-mentioned lithium manganese-based oxide is formed, the dissolution of transition metals from the surface of the above-mentioned lithium manganese-based oxide can be suppressed or alleviated, but on the contrary, it has been confirmed that the rate performance of lithium secondary batteries using the above-mentioned lithium manganese-based oxide as a positive electrode active material tends to decrease.

[0026] Therefore, an object of the present invention is to provide a positive electrode active material, which forms a coating for inhibiting or reducing the dissolution of transition metals from the surface of the above-mentioned lithium manganese-based oxide, and at the same time, through the above-mentioned coating, can prevent or alleviate the reduction in the life characteristics of a lithium secondary battery using the above-mentioned lithium manganese-based oxide as a positive electrode active material.

[0027] Specifically, an object of the present invention is to provide a positive electrode active material, which forms a coating portion containing fluorine and boron on at least a portion of the surface of the above-mentioned lithium manganese-based oxide, thereby improving the discharge capacity and charge / discharge efficiency that are reduced due to the excessive presence of lithium and manganese in the above-mentioned lithium manganese-based oxide.

[0028] Another object of the present invention is to provide a positive electrode active material which improves the rate performance and life efficiency of the lithium manganese-based oxide by controlling the contents of fluorine and boron in a coating portion formed on at least a portion of the surface of the lithium manganese-based oxide.

[0029] Another object of the present invention is to provide a positive electrode comprising a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode active material defined herein.

[0030] In addition, an object of the present invention is to provide a lithium secondary battery, which can prevent the reduction in rate performance and capacity caused by the excessive presence of lithium and manganese in the existing OLO by using the positive electrode defined in this article, and in particular, can achieve high stability by reducing the side reaction between the above-mentioned positive electrode active material and the electrolyte under storage or working environment at high voltage by forming a coating portion on the surface of the above-mentioned lithium manganese-based oxide.

[0031] Solutions to the problem

[0032] According to one aspect of the present invention for solving the above-mentioned technical problems, there is provided a positive electrode active material including a lithium manganese-based oxide in which a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group are solid-dissolved.

[0033] In the commercially available ternary lithium composite oxides composed of nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA), the phase belonging to the R3-m space group exists as a single phase. However, in the lithium-rich lithium manganese-based oxide defined in this article, the phase belonging to the C2 / m space group and the phase belonging to the R3-m space group are solid dissolved.

[0034] Furthermore, a coating portion containing fluorine and boron may be formed on at least a portion of the surface of the lithium manganese-based oxide.

[0035] The lithium manganese-based oxide as one of the components constituting the positive electrode active material may exist as secondary particles formed by agglomeration of a plurality of primary particles. In this case, at least one selected from fluorine and boron may have a concentration gradient decreasing from the surface portion to the center portion of the secondary particles.

[0036] In one embodiment, the coating portion may include a single coating layer in which fluorine and boron coexist. In another embodiment, the coating portion may include: (1) a first coating layer formed on at least a portion of the surface of the lithium manganese-based oxide and containing fluorine; and (2) a second coating layer formed on at least a portion of the surface of the first coating layer and containing boron. In another embodiment, the coating portion may include: (1) a first coating layer formed on at least a portion of the surface of the lithium manganese-based oxide and containing boron; and (2) a second coating layer formed on at least a portion of the surface of the first coating layer and containing fluorine.

[0037] In one embodiment, the lithium manganese-based oxide may be represented by the following Chemical Formula 1.

[0038] [Chemical formula 1]

[0039] Li(Li a M1 x M2 y ) 2-b X b

[0040] (in,

[0041] M1 is at least one selected from Ni and Mn,

[0042] M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd, M2 and M1 are not repeated, X is a halogen capable of replacing at least a part of the oxygen present in the above-mentioned lithium manganese-based oxide,

[0043] 0 <a≤0.7、0≤b≤0.1、0<x≤1、0≤y<1、0<x+y≤1)。

[0044] In another embodiment, the lithium manganese-based oxide may be represented by the following Chemical Formula 1-1.

[0045] [Chemical formula 1-1]

[0046] rLi2MnO 3-c X' c ·(1-r)Li a' M1 x' M2 y' O 2-b' X b'

[0047] (in,

[0048] M1 is at least one selected from Ni and Mn,

[0049] M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd, and M2 and M1 do not repeat,

[0050] X and X' are each independently a halogen capable of replacing at least a portion of the oxygen present in the lithium manganese-based oxide,

[0051] 0 <r≤0.7、0≤c≤0.1、0<a'≤1、0≤b'≤0.1、0<x'≤1、0≤y'<1、0<x'+y'≤1)

[0052] In addition, according to another aspect of the present invention, a positive electrode including a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector may be provided, wherein the positive electrode active material layer includes the positive electrode active material defined herein.

[0053] In addition, according to another aspect of the present invention, there is provided a lithium secondary battery comprising a positive electrode as defined herein, a negative electrode, a separation membrane interposed between the positive electrode and the negative electrode, and an electrolyte.

[0054] Effects of the Invention

[0055] According to the present invention, the limitations of existing lithium-rich lithium manganese-based oxides which are still inferior in electrochemical performance and / or stability compared with commercial ternary lithium composite oxides composed of nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA) can be improved.

[0056] Specifically, according to the present invention, a coating portion containing fluorine and boron is formed on at least a portion of the surface of the lithium manganese-based oxide, thereby improving the discharge capacity and charge / discharge efficiency that are reduced due to excessive lithium and manganese in the above lithium manganese-based oxide.

[0057] Therefore, by using the lithium manganese-based oxide according to the present invention as the positive electrode active material, the reduction in rate performance and capacity caused by the excessive presence of lithium and manganese in the existing OLO can be prevented. In particular, a lithium secondary battery with high stability can be provided by reducing the side reaction between the above-mentioned positive electrode active material and the electrolyte under storage or working environment at high voltage.

[0058] In addition to the above-described effects, specific effects of the present invention will be described while explaining specific details for implementing the present invention. DETAILED DESCRIPTION

[0059] Specific terms are defined herein for ease of understanding. Unless specifically defined herein, scientific terms and technical terms used herein should have the meanings commonly understood by those skilled in the art. In addition, it should be understood that as used herein, unless the context clearly indicates otherwise, the singular form is intended to include the plural form, and vice versa.

[0060] Hereinafter, a positive electrode active material including a lithium-rich lithium manganese-based oxide and a lithium secondary battery including the positive electrode active material according to some embodiments of the present invention will be described in more detail.

[0061] Positive active material

[0062] According to one aspect of the present invention, there is provided a positive electrode active material, the positive electrode active material comprising a lithium manganese-based oxide in which a phase belonging to a C2 / m space group and a phase belonging to an R3-m space group are solid-dissolved.

[0063] The phase belonging to the C2 / m space group and the phase belonging to the R3-m space group can be distinguished not only by the composition of each phase, but also by the characteristic peaks of each phase during XRD analysis. For example, the characteristic peak of the phase belonging to the C2 / m space group may appear in the region of 2θ=20.8±1°, and the characteristic peak of the phase belonging to the R3-m space group may appear in the region of 2θ=18.6±1°.

[0064] The lithium manganese-based oxide is a composite oxide in which a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group are solid-dissolved, and the phase belonging to the C2 / m space group and the phase belonging to the R3-m space group coexist in the lithium manganese-based oxide. In addition, the lithium manganese-based oxide is different from a composite oxide having a spinel crystal structure belonging to the Fd-3m space group (for example, LiMn2O4 or an oxide having a composition similar thereto).

[0065] The lithium manganese-based oxide contains at least lithium, manganese and a transition metal. The transition metal may include at least one selected from nickel, cobalt and aluminum. In addition, the lithium manganese-based oxide may include lithium, nickel and manganese, and may optionally further include a transition metal other than nickel.

[0066] The content of lithium in the above-mentioned lithium manganese-based oxide is greater than the sum of the contents of other transition metals (generally, the molar ratio of lithium to all metal elements except lithium in the lithium manganese-based oxide (lithium / metal molar ratio (Li / Metal molar ratio) is greater than 1), so it is also called lithium-rich layered oxide (overlithiated layered oxide; OLO).

[0067] In addition, since the content of manganese in the lithium manganese-based oxide is greater than the content of other transition metals, the lithium manganese-based oxide is also called a layered oxide with excess lithium and manganese.

[0068] Generally speaking, considering that the manganese content in the total metal elements other than lithium in the commercial nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA) ternary lithium composite oxide is less than 20 mol%, the above-mentioned lithium manganese-based oxide has a relatively high ratio of manganese in the total metal elements (for example, more than 50 mol%, more than 52 mol%, more than 53 mol% or more than 55 mol%) compared with the commercial ternary lithium composite oxide.

[0069] Furthermore, considering that the content of nickel in the total metal elements other than lithium in the commercialized nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA) ternary lithium composite oxide is more than 60 mol% (more than 80 mol% in the case of high-nickel lithium composite oxides), the above-mentioned lithium manganese-based oxide has a relatively low ratio of nickel in the total metal elements (for example, less than 50 mol%, less than 48 mol%, less than 46 mol%, less than 45 mol%, less than 44 mol%, less than 42 mol% or less than 40 mol%) compared with the commercialized ternary lithium composite oxide.

[0070] There is also a difference that the lithium / metal molar ratio measured from the lithium manganese-based oxide defined herein is greater than the lithium / metal molar ratio of a ternary lithium composite oxide such as nickel cobalt manganese (NCM) or nickel cobalt aluminum (NCA). For example, the lithium / metal molar ratio of a ternary lithium composite oxide such as nickel cobalt manganese (NCM) or nickel cobalt aluminum (NCA) appears to be close to 1. On the other hand, the lithium / metal molar ratio of the lithium manganese-based oxide defined herein is greater than 1, preferably 1.1 to 1.6, 1.1 to 1.5, 1.2 to 1.6 or 1.2 to 1.5.

[0071] Therefore, herein, the lithium manganese-based oxide may be defined as a composite oxide in which the manganese content in the metal elements other than lithium is 50 mol % or more, or may be defined as a composite oxide in which the manganese content in the metal elements other than lithium is 50 mol % or more and the nickel content is less than 50 mol %.

[0072] In addition, the lithium manganese-based oxide herein has a molar ratio of lithium to the total metal elements other than lithium greater than 1, or is 1.1 to 1.6, 1.1 to 1.5, 1.2 to 1.6 or 1.2 to 1.5, and is defined as a composite oxide in which the manganese content in the total metal elements other than lithium is 50 mol% or more, or a composite oxide in which the molar ratio of lithium to the total metal elements other than lithium is greater than 1, or is 1.1 to 1.6, 1.1 to 1.5, 1.2 to 1.6 or 1.2 to 1.5, the manganese content in the total metal elements other than lithium is 50 mol% or more, and the nickel content is less than 50 mol%.

[0073] Despite the above-mentioned difference in composition, the above-mentioned lithium manganese-based oxide can also be used as a composite metal oxide capable of intercalating / deintercalating lithium ions.

[0074] The lithium composite oxide contained in the positive electrode active material as defined herein may be present as particles including at least one primary particle.

[0075] When the lithium manganese-based oxide exists as a single primary particle, the lithium composite oxide may be referred to as a single particle. On the other hand, when the lithium manganese-based oxide exists as an aggregate formed by agglomerating a plurality of primary particles, the lithium composite oxide may be referred to as a secondary particle.

[0076] The positive electrode active material may include at least one selected from the group consisting of a lithium manganese-based oxide present as a single particle and a lithium manganese-based oxide present as a secondary particle formed by agglomerating a plurality of primary particles.

[0077] The primary particles constituting the above-mentioned lithium manganese-based oxide may have a rod (rod) shape, an elliptical shape and / or an irregular shape. In addition, unless specifically designed during the manufacturing process, primary particles of various shapes exist in the same positive electrode active material. In addition, the above-mentioned primary particles refer to particle units that do not appear to have grain boundaries when observed with a scanning electron microscope at a magnification of 5000 to 20000 times.

[0078] The average particle size of the primary particles constituting the lithium manganese-based oxide defined herein may be 0.05 μm to 5 μm, 0.05 μm to 1.0 μm, 0.1 μm to 1.0 μm, or 0.25 μm to 0.75 μm. At this time, as the average particle size of the primary particles, the average value of the length in the major axis direction and the length in the minor axis direction of the primary particles ([major axis length + minor axis length] / 2) may be used.

[0079] When the average particle size of the primary particles is less than 0.05 μm, the specific surface area of ​​the lithium manganese-based oxide (secondary particles) composed of the primary particles is large. In this case, the possibility of causing a side reaction between the lithium manganese-based oxide and the electrolyte during storage or operation of the lithium secondary battery increases.

[0080] On the other hand, when the average particle size of the primary particles is greater than 5 μm, the growth of the primary particles is excessively induced, so the diffusion path of lithium ions in the primary particles also becomes longer. When the diffusion path of lithium ions in the primary particles is too long, the mobility of lithium ions in the primary particles and the diffusivity of lithium ions through the primary particles are reduced, which becomes a cause of increasing the resistance of the lithium composite oxide (secondary particles) composed of the primary particles.

[0081] Therefore, in order to prevent the mobility of lithium ions in the above-mentioned primary particles and the diffusivity of lithium ions through the above-mentioned primary particles from decreasing while reducing the specific surface area of ​​the above-mentioned lithium manganese-based oxide, the average particle size of the above-mentioned primary particles is preferably 0.05μm to 5μm, 0.05μm to 1.0μm, 0.1μm to 1.0μm or 0.25μm to 0.75μm.

[0082] When the lithium manganese-based oxide exists as secondary particles formed by the aggregation of multiple primary particles, the average particle size of the secondary particles can be 0.5μm to 15μm, 1.0μm to 15μm, 2.0μm to 15μm, 3.0μm to 15μm, 4.0μm to 15μm or 5.0μm to 15μm. The average particle size of the secondary particles can vary according to the number of the primary particles constituting the secondary particles. The average particle size (D50) of the secondary particles can be measured using a laser diffraction method. For example, after the secondary particles are dispersed in a dispersion medium, they are introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000), irradiated with ultrasonic waves of about 28kHz at a power of 60W, and then after obtaining a volume cumulative particle size distribution chart, the particle size equivalent to 50% of the volume cumulative amount is obtained to achieve measurement.

[0083] Unless otherwise defined, the term "surface of the primary particle" as used herein refers to the outer surface of the primary particle exposed to the outside. Similarly, the term "surface of the secondary particle" as used herein refers to the outer surface of the secondary particle exposed to the outside. In this case, the "surface of the secondary particle" formed by the agglomeration of multiple primary particles is equivalent to the exposed surface of the primary particle existing on the surface of the secondary particle.

[0084] In addition, unless otherwise defined, the term "surface portion of a particle" as used herein refers to a region relatively close to the "outermost surface" of a particle, and "center portion of a particle" refers to a region relatively close to the "exact center" of a particle compared to the above-mentioned "surface portion". Therefore, the "surface portion of a primary particle" refers to a region relatively close to the "outermost surface" of the above-mentioned primary particle, and the "center portion of a primary particle" refers to a region relatively close to the "exact center" of the above-mentioned primary particle compared to the above-mentioned "surface portion". Similarly, the "surface portion of a secondary particle" refers to a region relatively close to the "outermost surface" of the above-mentioned secondary particle, and the "center portion of a secondary particle" refers to a region relatively close to the "exact center" of the above-mentioned secondary particle compared to the above-mentioned "surface portion".

[0085] At this time, a region other than the “surface portion of the particle” within any particle can be defined as the “center portion of the particle”.

[0086] For example, when the radius of the primary particle is r, the region at a distance of 0r to 0.5r from the surface of the primary particle can be defined as the surface portion of the primary particle, and the region at a distance of 0r to 0.5r from the exact center of the primary particle can be defined as the central portion of the primary particle. If the radius of the primary particle is 0.5 μm, the surface portion of the primary particle can be defined as the region at a distance of 0 μm to 0.25 μm from the surface of the primary particle, and the central portion of the primary particle can be defined as the region at a distance of 0 μm to 0.25 μm from the exact center of the primary particle.

[0087] In addition, as needed, when the radius of the above-mentioned primary particle is r, the area with a distance of 0r to 0.1r or 0r to 0.2r from the surface of the above-mentioned primary particle can be defined as the surface part of the above-mentioned primary particle, and the area with a distance of 0r to 0.2r or 0r to 0.5r from the exact center of the above-mentioned primary particle can be defined as the central part of the above-mentioned primary particle.

[0088] Similarly, when the radius of the secondary particle is r, the region at a distance of 0r to 0.5r from the surface of the secondary particle can be defined as the surface portion of the secondary particle, and the region at a distance of 0r to 0.5r from the exact center of the secondary particle can be defined as the central portion of the secondary particle. If the radius of the secondary particle is 2.0 μm, the surface portion of the secondary particle can be defined as the region at a distance of 0 μm to 1.0 μm from the surface of the secondary particle, and the central portion of the secondary particle can be defined as the region at a distance of 0 μm to 1.0 μm from the exact center of the secondary particle.

[0089] In addition, as needed, when the radius of the above-mentioned secondary particle is r, the region with a distance of 0r to 0.1r or 0r to 0.2r from the surface of the above-mentioned secondary particle can be defined as the surface portion of the above-mentioned secondary particle, and the region with a distance of 0r to 0.2r or 0r to 0.5r from the exact center of the above-mentioned secondary particle can be defined as the central portion of the above-mentioned secondary particle.

[0090] The lithium manganese-based oxide defined herein may be a lithium-rich lithium manganese-based oxide represented by the following Chemical Formula 1. The composition represented by the following Chemical Formula 1 may represent an average composition reflecting the composition of the coating layer present in at least a portion of the surface of the lithium manganese-based oxide.

[0091] [Chemical formula 1]

[0092] Li(Li a M1 x M2 y ) 2-b X b

[0093] Wherein, M1 is at least one selected from Ni and Mn, M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd, M2 and M1 are not repeated, X is a halogen that can replace at least a part of the oxygen present in the above-mentioned lithium manganese-based oxide, and 0 <a≤0.7、0≤b≤0.1、0<x≤1、0≤y<1、0<x+y≤1。

[0094] As the kind of halogen that can be used as X, referring to the periodic table, F, Cl, Br and / or I etc. can be used, and preferably F can be used.

[0095] In another embodiment, the lithium manganese-based oxide may be represented by the following chemical formula 1-1. The composition represented by the following chemical formula 1-1 may represent an average composition reflecting the composition of the coating layer present in at least a portion of the surface of the lithium manganese-based oxide.

[0096] [Chemical formula 1-1]

[0097] rLi2MnO 3-c X' c ·(1-r)Li a' M1 x' M2 y' O 2-b' X b'

[0098] Wherein, M1 is at least one selected from Ni and Mn, M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd, M2 does not overlap with M1, X and X' are each independently a halogen capable of replacing at least a portion of the oxygen present in the above-mentioned lithium manganese-based oxide, <r≤0.7、0≤c≤0.1、0<a'≤1、0≤b'≤0.1、0<x'≤1、0≤y'<1、0<x'+y'≤1。

[0099] As the kind of halogen that can be used as X and X', referring to the periodic table, F, Cl, Br and / or I etc. can be used, and preferably, F can be used.

[0100] In the above Chemical Formula 1 and the above Chemical Formula 1-1, when M1 is Ni, M2 may include Mn, and when M1 is Mn, M2 may include Ni. In addition, when M1 is Ni and Mn, M2 may not exist, or, if present, may be an element other than Ni and Mn.

[0101] That is, when M1 is Ni, M2 may include at least one selected from Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd (preferably at least one selected from Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo and W, more preferably at least one selected from Co, P, B, Si, Ti, Zr and W, and even more preferably at least one selected from P, B and Si) and Mn.

[0102] When M1 is Mn, M2 may include at least one selected from Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd (preferably at least one selected from Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo and W, more preferably at least one selected from Co, P, B, Si, Ti, Zr and W, even more preferably at least one selected from P, B and Si) and Ni.

[0103] When M1 is Ni and Mn, M2 may include at least one selected from Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd, preferably, may include at least one selected from Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo and W, more preferably, may include at least one selected from Co, P, B, Si, Ti, Zr and W, even more preferably, may include at least one selected from P, B and Si.

[0104] The lithium manganese-based oxide represented by the above chemical formula 1 or the above chemical formula 1-1 may optionally include cobalt. In addition, when the above lithium manganese-based oxide includes cobalt, the molar number of the above cobalt relative to the molar number of the entire metal element in the above lithium manganese-based oxide may be 20% or less, preferably, 15% or less, and more preferably, 10% or less. In another case, the lithium manganese-based oxide represented by the above chemical formula 1 may have a cobalt-free composition that does not contain cobalt.

[0105] The lithium / metal molar ratio measured from the lithium manganese-based oxide represented by the above chemical formula 1 or the above chemical formula 1-1 may be greater than 1, preferably, it may be 1.1 to 1.6, 1.1 to 1.5, 1.2 to 1.6 or 1.2 to 1.5. Only when the lithium / metal molar ratio measured from the above lithium manganese-based oxide is at least greater than 1, a lithium-rich lithium manganese-based oxide can be formed. In addition, in order to allow the above lithium manganese-based oxide to properly form a solid solution of a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group, and at the same time exert a high capacity under a high voltage working environment, the lithium / metal molar ratio of the above lithium manganese-based oxide is preferably 1.1 to 1.6, 1.1 to 1.5, 1.2 to 1.6 or 1.2 to 1.5.

[0106] In addition, in order to properly form a solid solution of a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group, the manganese content in the entire metal elements other than lithium present in the lithium manganese-based oxide represented by the above Chemical Formula 1 or the above Chemical Formula 1-1 is preferably 50 mol% or more. In order to make the above-mentioned lithium manganese-based oxide have OLO characteristics showing high capacity under a high voltage operating environment, the content of manganese in the entire metal elements except lithium present in the above-mentioned lithium manganese-based oxide can be 50 mol% or more and less than 80 mol%, 51 mol% or more and less than 80 mol%, 52 mol% or more and less than 80 mol%, 53 mol% or more and less than 80 mol%, 54 mol% or more and less than 80 mol%, 55 mol% or more and less than 80 mol%, 50 mol% or more and 75 mol%, 51 mol% or more and 75 mol%, 52 mol% or more and 75 mol%, 53 mol% or more and 75 mol%, 54 mol% or more and 75 mol%, 55 mol% or more and 75 mol%,

[0107] When the manganese content in the above-mentioned lithium manganese-based oxide exceeds 80 mol%, a phase change may occur during the formation and / or operation of the lithium secondary battery due to the movement of the transition metal (especially manganese) in the above-mentioned lithium manganese-based oxide. The above-mentioned phase change forms a spinel phase, and the above-mentioned spinel acting as an impurity in the above-mentioned lithium manganese-based oxide can cause a decrease in charge / discharge capacity or voltage decay when the lithium secondary battery is cycled. In addition, when the manganese content in the above-mentioned lithium manganese-based oxide exceeds 80 mol%, it may be difficult to fully produce a phase belonging to the R3-m space group.

[0108] In order to properly form a solid solution in which a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group are solid-dissolved, the content of nickel in the entire metal elements other than lithium present in the lithium manganese-based oxide represented by the above Chemical Formula 1 or the above Chemical Formula 1-1 can be less than 50 mol%, less than 48 mol%, less than 46 mol%, less than 45 mol%, less than 44 mol%, less than 42 mol% or less than 40 mol%.

[0109] When the nickel content in the above-mentioned lithium manganese-based oxide is above 50 mol%, it is difficult to fully form the C2 / m phase, or the phase belonging to the C2 / m space group and the phase belonging to the R3-m space group may not form a sufficient solid solution, resulting in phase separation during the formation and / or operation of the lithium secondary battery.

[0110] Generally, in a commercially available ternary lithium composite oxide composed of nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA), a phase belonging to the R3-m space group exists as a single-phase.

[0111] On the other hand, the lithium-rich lithium manganese-based oxide represented by the above Chemical Formula 1 or the above Chemical Formula 1-1 is composed of rLi2MnO 3-c X' c The oxides of the phase belonging to the C2 / m space group (hereinafter referred to as "C2 / m phase") and (1-r)Li a M1 x M2 y O 2-b X b The composite oxide exists as a solid solution of an oxide of a phase belonging to the R3-m space group (hereinafter referred to as "R3-m phase"). For example, the lithium manganese-based oxide may exist as a solid solution of an oxide of the C2 / m phase and an oxide of the R3-m phase.

[0112] In this case, a composite oxide in which a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group are simply physically and / or chemically combined or attached does not correspond to a solid solution as defined herein.

[0113] For example, coating a surface with a metal oxide having a phase belonging to the C2 / m space group with a metal oxide having a phase belonging to the R3-m space group by mixing a metal oxide having a phase belonging to the C2 / m space group and a metal oxide having a phase belonging to the R3-m space group does not correspond to the solid solution defined in this article.

[0114] In addition, in the lithium manganese-based oxide represented by the above chemical formula 1-1, when r exceeds 0.7, Li2MnO as an oxide of the C2 / m phase in the above lithium manganese-based oxide 3-c X' c The ratio of R3-m phase oxide to C2-m phase oxide is excessively increased, which may increase the irreversible capacity and resistance of the positive electrode active material, thereby reducing the discharge capacity. That is, in order to fully activate the C2 / m phase oxide with relatively high resistance in the above-mentioned lithium manganese-based oxide to improve the surface dynamics, the R3-m phase oxide is preferably present in a predetermined ratio or more.

[0115] In one embodiment, a coating portion containing fluorine and boron may be formed on at least a portion of the surface of the lithium manganese-based oxide. In the case where the lithium manganese-based oxide is a secondary particle formed by agglomeration of multiple primary particles, the coating portion may cover at least a portion of the surface of the primary particle and / or the secondary particle. By forming a coating portion containing fluorine and boron on the surface of the lithium manganese-based oxide, the side reaction with the electrolyte occurring on the surface of the lithium manganese-based oxide is reduced, and at the same time, the charge transfer and / or diffusivity (i.e., surface dynamics) of lithium ions on the surface of the lithium manganese-based oxide can be alleviated and / or prevented from decreasing.

[0116] The surface where adjacent primary particles in the secondary particle are in contact may be referred to as the interface between the primary particles, and the interface between the primary particles may be defined as the grain boundary between the primary particles. Furthermore, the primary particles may be separated from adjacent primary particles in the secondary particle to form internal voids.

[0117] The coating portion is defined as a region where fluorine and boron exist on the surface of the primary particle and / or the secondary particle, and the coating portion may be formed in whole or in part on the surface of the primary particle and / or the secondary particle. When the coating portion is formed on the surface of the primary particle and / or the secondary particle, the shape of the coating may be called an island.

[0118] Furthermore, fluorine and boron may exist in a state of being physically and / or chemically bonded in the form of chemicals on the surface of the primary particles and / or the secondary particles, or may exist in a state of being partially solid-solved.

[0119] As fluorine and boron diffuse from the surface of the secondary particle toward the center of the secondary particle along the grain boundary between the primary particles, the coating layer existing inside the secondary particle may be formed.

[0120] Specifically, the main compound constituting the coating portion (e.g., a fluorine-containing compound and / or a boron-containing compound) may exist in a state of diffusion from the surface portion of the secondary particle to the center portion of the secondary particle. Furthermore, as the coating portion diffuses from the surface portion of the secondary particle to the center portion of the secondary particle, the element mainly contained in the coating portion (e.g., fluorine and / or boron) may present a concentration gradient that decreases from the surface portion of the secondary particle to the center portion of the secondary particle.

[0121] In one embodiment, the coating portion may include a fluorine-containing compound. At this time, a representative example of the fluorine-containing compound is LiF. LiF can be formed by the reaction of a fluorine-containing polymer with lithium impurities (e.g., LiOH and Li2CO3) present on the surface of the lithium manganese-based oxide. The reaction between the fluorine-containing polymer and the lithium impurities can occur by heat treatment, and the carbon in the fluorine-containing polymer can form a carbonaceous matrix. Wherein, a carbonaceous matrix can be formed when the fluorine-containing polymer is carbonized, and LiF can be present in the carbonaceous matrix in a dispersed state.

[0122] When a fluorine-containing compound such as LiF is formed in the coating portion, the content of lithium impurities present on the surface of the lithium manganese-based oxide can be reduced. In addition, due to the passivation effect caused by LiF formed on the surface of the lithium manganese-based oxide, the decomposition of the electrolyte occurring on the surface of the lithium manganese-based oxide can be reduced and / or suppressed.

[0123] The fluorine may be present in an amount of greater than 100 ppm and 3,500 ppm or less, preferably 150 ppm to 3,500 ppm, and more preferably 150 ppm to 1,100 ppm, based on the total weight of the positive electrode active material.

[0124] The presence of fluorine in an amount of less than 100 ppm based on the total weight of the positive electrode active material means that LiF is not fully formed on the surface of the lithium manganese-based oxide. In this case, it is not only difficult to fully reduce the surface impurities of the lithium manganese-based oxide, but also the protective effect on the surface of the lithium manganese-based oxide may be insufficient. On the other hand, when the fluorine is present in an amount greater than 3,500 ppm based on the total weight of the positive electrode active material, the resistance of the lithium manganese-based oxide is excessively increased, thereby possibly reducing the overall electrochemical performance of the lithium secondary battery using the lithium manganese-based oxide as the positive electrode active material.

[0125] In one embodiment, the coating portion may include a boron-containing compound. Representative examples of the boron-containing compound include B2O3, H α B β O γ (0<α<10, 0<β<10, 0<γ<20) and Li α' B β' O γ' (0<α'<10, 0<β'<10, 0<γ'<20).

[0126] The boron content may be greater than 50 ppm and less than 3,000 ppm, preferably 100 ppm to 3,000 ppm, and more preferably 100 ppm to 1,300 ppm, based on the total weight of the positive electrode active material.

[0127] Based on the total weight of the above-mentioned positive electrode active material, the presence of the above-mentioned boron in an amount of 50ppm or less means that the boron-containing compound is not fully formed on the surface of the above-mentioned lithium manganese-based oxide. In this case, it may be difficult to fully suppress the dissolution of transition metals from the above-mentioned lithium manganese-based oxide. On the other hand, when the above-mentioned boron is present in an amount greater than 3,000ppm based on the total weight of the above-mentioned positive electrode active material, the surface kinetic properties of the above-mentioned lithium manganese-based oxide may be reduced, or the conductivity of the above-mentioned lithium manganese-based oxide may be reduced. In addition, the problem of rapid increase in gas generation in the above-mentioned lithium secondary battery may occur.

[0128] As described above, the fluorine-containing compounds and boron-containing compounds contained in the above-mentioned coating portion can form a gradient from the surface portion of the above-mentioned secondary particles to the central portion of the above-mentioned secondary particles, and the concentration gradient of the fluorine-containing compounds and boron-containing compounds thus formed can be used as a lithium ion diffusion path, that is, a two-dimensional and / or three-dimensional path for lithium ions to diffuse in the above-mentioned lithium manganese-based oxide.

[0129] As lithium ion diffusion paths are formed in the lithium manganese-based oxide, resistance to movement of lithium ions through the lithium manganese-based oxide is reduced, thereby contributing to improved rate performance of a lithium secondary battery using the lithium manganese-based oxide as a positive electrode active material.

[0130] In one embodiment, the coating portion may include a single coating layer in which fluorine and boron coexist. In another embodiment, the coating portion may include: (1) a first coating layer formed on at least a portion of the surface of the lithium manganese-based oxide and containing fluorine; and (2) a second coating layer formed on at least a portion of the surface of the first coating layer and containing boron. In another embodiment, the coating portion may include: (1) a first coating layer formed on at least a portion of the surface of the lithium manganese-based oxide and containing boron; and (2) a second coating layer formed on at least a portion of the surface of the first coating layer and containing fluorine. The first coating layer and the second coating layer may be defined according to the order in which the coating layers containing the fluorine-containing compound and the boron-containing compound are formed, respectively.

[0131] As defined herein, the coating portion may include fluorine and boron, and specifically, may include a fluorine-containing compound and a boron-containing compound.

[0132] The weight ratio of the fluorine to the boron calculated based on the total weight of the positive electrode active material may be 1:0.03 to 1:25, and preferably, 1:1.2 to 1:25.

[0133] The ratio of the weight of the above-mentioned boron to the weight of the above-mentioned fluorine calculated based on the total weight of the above-mentioned positive electrode active material being greater than 25 means that in the above-mentioned positive electrode active material, especially in the above-mentioned coating portion, the content of the above-mentioned fluorine is too little compared with the content of the above-mentioned boron, or the content of the above-mentioned boron is too much compared with the content of the above-mentioned fluorine. If the above-mentioned fluorine content in the above-mentioned coating portion is too small, it is not only difficult to fully reduce the surface impurities of the above-mentioned lithium manganese-based oxide, but also the protective effect on the surface of the above-mentioned lithium manganese-based oxide may be insufficient. On the other hand, when the content of the above-mentioned boron in the above-mentioned coating portion is too much, the surface dynamic properties of the above-mentioned lithium manganese-based oxide may be reduced, or the conductivity of the above-mentioned lithium manganese-based oxide may be reduced.

[0134] The weight ratio of the above-mentioned boron to the above-mentioned fluorine calculated based on the total weight of the above-mentioned positive electrode active material is less than 0.03, which means that in the above-mentioned positive electrode active material, especially in the above-mentioned coating part, the content of the above-mentioned fluorine and the content of the above-mentioned boron are too much, or the content of the above-mentioned boron and the content of the above-mentioned fluorine are too little. If the above-mentioned fluorine content in the above-mentioned coating part is too high, the resistance of the above-mentioned lithium manganese-based oxide increases excessively, and the overall electrochemical performance of the lithium secondary battery using the above-mentioned lithium manganese-based oxide as the positive electrode active material may be reduced. On the other hand, when the above-mentioned boron content in the above-mentioned coating part is too little, it is difficult to fully suppress the dissolution of the transition metal from the above-mentioned lithium manganese-based oxide, resulting in a decrease in the life characteristics of the lithium secondary battery using the above-mentioned lithium manganese-based oxide as the positive electrode active material.

[0135] Lithium secondary battery

[0136] According to another aspect of the present invention, a positive electrode including a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector may be provided. The positive electrode active material layer may include a lithium manganese-based oxide having a coating portion formed on at least a portion of the surface according to various embodiments of the present invention as a positive electrode active material.

[0137] Therefore, the detailed description of the lithium manganese-based oxide will be omitted, and only the remaining components not mentioned above will be described below. In addition, for the sake of convenience, the lithium manganese-based oxide will be referred to as a positive electrode active material.

[0138] The positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, or the surface of aluminum or stainless steel may be treated with carbon, nickel, titanium, silver, etc. In addition, the positive electrode current collector may generally have a thickness of 3 μm to 500 μm, and fine concavoconvexities may be formed on the surface of the current collector to improve the binding force of the positive electrode active material. For example, it may be used in various forms such as a film, a sheet, a foil, a net, a porous body, a foam, and a nonwoven body.

[0139] The positive electrode active material layer may be prepared by coating a positive electrode slurry composition including the positive electrode active material, a conductive material, and optionally a binder as required, on the positive electrode current collector.

[0140] In this case, the content of the positive electrode active material can be 80 wt % to 99 wt %, more specifically 85 wt % to 98.5 wt % relative to the total weight of the positive electrode active material layer. When the positive electrode active material is included in the above content range, excellent capacity performance can be shown, but it is not limited thereto.

[0141] The above-mentioned conductive materials are used to impart conductivity to the electrode. In the battery formed, as long as they do not cause chemical changes and have electronic conductivity, they can be used without limitation. As specific examples, graphite such as natural graphite or artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, etc., and one of them or a mixture of two or more thereof can be used. The above-mentioned conductive material may be included in an amount of 0.1% to 15% by weight relative to the total weight of the positive electrode active material layer.

[0142] The above-mentioned binder plays a role in improving the adhesion between multiple positive electrode active material particles and the bonding force between the positive electrode active material and the collector. As a specific example, polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile (polyacrylonitrile), carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM), sulfonated ethylene propylene diene rubber, styrene butadiene rubber (SBR), fluororubber or various copolymers thereof, etc., can be used. One or a mixture of two or more thereof. Relative to the total weight of the positive electrode active material layer, 0.1% to 15% by weight of the above-mentioned binder may be included.

[0143] In addition to using the above-mentioned positive electrode active material, the above-mentioned positive electrode can be prepared according to a common positive electrode preparation method. Specifically, it can be prepared by coating a positive electrode slurry composition on a positive electrode collector and then drying and rolling it. The above-mentioned positive electrode slurry composition is prepared by dissolving or dispersing the above-mentioned positive electrode active material in a solvent and selectively dissolving or dispersing a binder and a conductive material in a solvent.

[0144] The above-mentioned solvent may be a solvent commonly used in the art, and examples thereof include dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone or water, and a mixture of one or more thereof may be used. Considering the coating thickness and preparation yield of the slurry, the amount of the above-mentioned solvent used is sufficient to dissolve or disperse the above-mentioned positive electrode active material, conductive material and binder and have a viscosity that can show excellent thickness uniformity when applied to prepare the positive electrode.

[0145] Furthermore, in another embodiment, the positive electrode may be prepared by casting the positive electrode slurry composition on a separate support, and then laminating a thin film obtained by peeling the support on a positive electrode collector.

[0146] In addition, according to another aspect of the present invention, an electrochemical device comprising the positive electrode described above can be provided. Specifically, the electrochemical device described above can be a battery, a capacitor, etc., and more specifically, can be a lithium secondary battery.

[0147] Specifically, the lithium secondary battery may include a positive electrode, a negative electrode disposed opposite to the positive electrode, and a separation membrane and an electrolyte disposed between the positive electrode and the negative electrode. The positive electrode is the same as the above description, so for convenience, the specific description is omitted, and only the remaining configuration not described above is described below.

[0148] The lithium secondary battery may further include: a battery container for accommodating the electrode assembly of the positive electrode, the negative electrode and the separation membrane; and a sealing member for sealing the battery container.

[0149] The negative electrode may include a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0150] The negative electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. In addition, the negative electrode current collector can usually have a thickness of 3 μm to 500 μm. Similar to the positive electrode current collector, the binding force of the negative electrode active material can be strengthened by forming fine concave and convex on the surface of the collector. For example, it can be used in various forms such as a film, a sheet, a foil, a net, a porous body, a foam, and a non-woven body.

[0151] The negative electrode active material layer may be prepared by coating a negative electrode slurry composition including the negative electrode active material and a conductive material and optionally including a binder as required on the negative electrode collector.

[0152] As the negative electrode active material, a compound capable of reversibly inserting and extracting lithium can be used. Specific examples include carbon materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metal compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloy, Sn alloy, or Al alloy; and SiO β(0<β<2), SnO2, vanadium oxide, lithium vanadium oxide, metal oxides capable of being doped and dedoped with lithium; or composites containing the above metal compounds and carbon materials such as Si-C composites or Sn-C composites, etc., and one or a mixture of two or more of them can be used. In addition, as the above-mentioned negative electrode active material, a metal lithium film can also be used. In addition, both low-crystalline carbon and high-crystalline carbon can be used as carbon materials. Representative low-crystalline carbons are soft carbon and hard carbon, and representative high-crystalline carbons are amorphous, plate-like, flaky, spherical or fibrous natural graphite or artificial graphite, condensed graphite (Kishgraphite), pyrolytic carbon (pyrolytic carbon), mesophase pitch based carbon fiber (mesophase pitch based carbon fiber), mesophase carbon microbeads (meso-carbon microbeads), mesophase pitch (Mesophase pitches) and petroleum or coal tar pitch derived cokes (petroleum or coal tar pitch derived cokes) and other high-temperature calcined carbons.

[0153] The negative electrode active material layer may contain 80 wt % to 99 wt % of the negative electrode active material, based on the total weight of the negative electrode active material layer.

[0154] The binder is a component that helps to bind the conductive material, the active material and the collector. Usually, based on the total weight of the negative electrode active material layer, 0.1 wt % to 10 wt % of the binder can be added. Examples of such binders include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber, sulfonated ethylene propylene diene rubber, styrene butadiene rubber, nitrile rubber, fluororubber, and various copolymers thereof.

[0155] The conductive material is a component used to further improve the conductivity of the negative electrode active material. Based on the total weight of the negative electrode active material layer, the conductive material can be added in an amount of 10% by weight or less, preferably 5% by weight or less. There are no particular restrictions on such conductive materials as long as they do not induce chemical changes in the corresponding battery and have conductivity. For example, graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black; conductive fibers such as carbon fibers or metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives, etc. can be used.

[0156] In one embodiment, the negative electrode active material layer may be prepared by coating a negative electrode slurry composition on a negative electrode collector and drying it, wherein the negative electrode slurry composition is prepared by dissolving or dispersing the negative electrode active material in a solvent and selectively dissolving or dispersing a binder and a conductive material in a solvent, or by casting the negative electrode slurry composition on a separate support and laminating a thin film obtained by peeling off the support on the negative electrode collector.

[0157] On the other hand, in the above-mentioned lithium secondary battery, the separation membrane is used to separate the negative electrode and the positive electrode and provide a mobile channel for lithium ions. As long as the separation membrane commonly used in the lithium secondary battery, it can be used without restriction, especially, preferably, for the ion movement of the electrolyte, the impedance is low and there is excellent electrolyte moisture-containing capacity. Specifically, a porous polymer film can be used, for example, a porous polymer film prepared by polyolefin polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers and ethylene / methacrylate copolymers or their two or more layers of stacked structures. In addition, a common porous non-woven fabric can also be used, for example, a non-woven fabric made of high melting point glass fiber, polyethylene terephthalate fiber, etc. In addition, in order to ensure heat resistance or mechanical strength, a separation membrane coated with a ceramic component and a polymer substance can also be used, which can be selectively used with a single layer or multilayer structure.

[0158] Furthermore, examples of the electrolyte used in the present invention include, but are not limited to, organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in preparing lithium secondary batteries.

[0159] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0160] As the above-mentioned organic solvent, any organic solvent that can act as a medium for the movement of ions involved in the electrochemical reaction of the battery can be used without limitation. Specifically, as the above-mentioned organic solvent, ester solvents such as methylacetate, ethylacetate, γ-butyrolactone, ε-caprolactone, etc.; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (EPC), etc. can be used. Carbonate solvents such as nate, PC, etc.; alcohol solvents such as ethanol and isopropanol; nitriles such as R-CN (r is a straight-chain, branched or cyclic hydrocarbon group with 2 to 20 carbon atoms, which may contain a double-bonded aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; or sulfolane, etc. Among them, carbonate solvents are preferred, and more preferably, a mixture of cyclic carbonates (such as ethylene carbonate or propylene carbonate, etc.) with high ionic conductivity and high dielectric constant that can improve the charge and discharge performance of the battery, and low-viscosity linear carbonate compounds (such as ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate, etc.). In this case, when the cyclic carbonate and the chain carbonate are mixed in a volume ratio of about 1:1 to about 1:9, excellent electrolyte performance can be shown.

[0161] The above-mentioned lithium salt can be used without limitation as a compound that can provide lithium ions used in a lithium secondary battery. Specifically, the above-mentioned lithium salt can be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI or LiB(C2O4)2, etc. Preferably, the concentration of the above-mentioned lithium salt is used in the range of 0.1M to 2.0M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, and therefore, excellent electrolyte performance can be shown, and lithium ions can be effectively moved.

[0162] When the electrolyte used herein is a solid electrolyte, for example, a solid inorganic electrolyte such as a sulfide solid electrolyte, an oxide solid electrolyte, a nitride solid electrolyte, or a halide solid electrolyte can be used, and preferably a sulfide solid electrolyte can be used.

[0163] As the material of the sulfide solid electrolyte, a solid electrolyte containing Li, an X element (wherein X is at least one selected from P, As, Sb, Si, Ge, Sn, B, Al, Ga and In) and S can be used. Examples of the above-mentioned sulfide solid electrolyte materials include Li2S-P2S5, Li2S-P2S-LiX (wherein X is a halogen element such as I or Cl), Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (where m and n are integers, Z is Ge, Zn or Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li p MO q (wherein p and q are integers, and M is P, Si, Ge, B, Al, Ga or In), etc.

[0164] The solid electrolyte, preferably a sulfide-based solid electrolyte, may be in an amorphous state, a crystalline state, or a mixed state of the amorphous state and the crystalline state.

[0165] Examples of materials for oxide-based solid electrolytes include Li7La3Zr2O 12 , Li 7-x LqCy 1-x Nb x O 12 , Li 7- 3x La3Zr2Al x O 12 , Li 3x La 2 / 3-x TiO3、Li 1+x Al x Ti 2-x (PO4)3、Li 1+x Al x Ge 2-x (PO4)3, Li3PO4, Li3+x PO 4-x N x (LiPON), Li 2+2x Zn 1-x GeO4(LISICON), etc.

[0166] The solid electrolyte may be arranged between the positive electrode and the negative electrode as a separate layer (solid electrolyte layer). In addition, the solid electrolyte may be partially contained in the positive electrode active material layer of the positive electrode independently of the solid electrolyte layer, or the solid electrolyte may be partially contained in the negative electrode active material layer of the negative electrode independently of the solid electrolyte layer.

[0167] In addition to the above electrolyte components, the electrolyte may further include one or more additives such as halogenated alkylene carbonate compounds such as bisfluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol or aluminum chloride, etc., for the purpose of improving the life characteristics of the battery, inhibiting the reduction of the battery capacity, and increasing the discharge capacity of the battery. In this case, the above additives may be included in an amount of 0.1 wt % to 5 wt % relative to the total weight of the electrolyte.

[0168] As described above, the lithium secondary battery containing the positive electrode active material of the present invention stably shows excellent discharge capacity, output characteristics and life characteristics, and can therefore be used in portable devices such as mobile phones, notebook computers, digital cameras, and electric vehicles such as hybrid electric vehicles (HEV).

[0169] The external shape of the lithium secondary battery according to the present invention is not particularly limited, and may be a cylindrical shape using a can, a prismatic shape, a pouch shape, a coin shape, etc. Also, preferably, the lithium secondary battery can be used not only as a battery cell used as a power source for small devices, but also as a unit battery of a medium or large battery module including a plurality of battery cells.

[0170] According to another aspect of the present invention, a battery module including the above-mentioned lithium secondary battery as a unit cell and / or a battery pack including the same may be provided.

[0171] The battery module or the battery pack can be used as a power tool; an electric vehicle including an electric vehicle (EV), a hybrid electric vehicle and a plug-in hybrid electric vehicle (PHEV); or a power source for one or more medium or large devices in a power storage system.

[0172] Hereinafter, the present invention will be described in more detail by way of examples. However, these examples are only for illustrating the present invention, and the scope of the present invention should not be construed as being limited by these examples.

[0173] Preparation Example 1. Preparation of positive electrode active material

[0174] Comparative Example 1

[0175] (a) Precursor preparation

[0176] A mixed aqueous solution of NiSO4·6H2O and MnSO4·H2O in a molar ratio of 40:60, NaOH and NH4OH were added to the reactor and stirred. The temperature in the reactor was maintained at 45°C, and the precursor synthesis reaction was carried out while N2 gas was introduced into the reactor. After the reaction was completed, the Ni with an average particle size of 3.5 μm was obtained by washing and dehydration. 0.4 Mn 0.6 (OH)2 precursor.

[0177] (b) Precursor coating

[0178] In the reactor in which the precursor obtained in step (a) is stirred, an aqueous solution of NiSO4·6H2O, NaOH and NH4OH are added. At this time, NiSO4·6H2O is weighed to 5 mol% and then added. After the reaction is completed, washing and dehydration are performed, and then drying is performed at 150° C. for 14 hours to obtain a coated precursor.

[0179] (c) First heat treatment

[0180] The sintering furnace in the air atmosphere was heated at a rate of 2°C / min, and then the precursor obtained in step (b) was heat-treated for 5 hours while maintaining 550°C, followed by furnace cooling to obtain a precursor in an oxide state.

[0181] (d) Second heat treatment

[0182] A mixture was prepared by mixing the precursor in an oxide state obtained in step (c) with LiOH (molar ratio of lithium / (metal other than lithium) = 1.22) as a lithium raw material material.

[0183] Next, the sintering furnace in an O2 atmosphere was heated at a rate of 2°C / min, and then the mixture was heat-treated for 8 hours while maintaining 900°C, and then furnace-cooled to obtain a lithium-rich lithium manganese-based oxide.

[0184] Reference Example 1

[0185] After mixing the lithium manganese-based oxide prepared in Comparative Example 1 and H3BO3 (weighed so that the boron content based on the amount of H3BO3 added as a raw material is 1,300 ppm relative to the total weight of the above-mentioned lithium manganese-based oxide), an O2 atmosphere is maintained in a sintering furnace, the temperature is raised to 400°C at a rate of 4.4°C / min, heat treated for 8 hours, classified and crushed to obtain a lithium manganese-based oxide having a boron-containing coating portion (including lithium borate) formed on the surface.

[0186] Reference Example 2

[0187] After mixing the lithium manganese-based oxide and PVDF prepared in Comparative Example 1 (weighed so that the fluorine content based on the amount of PVDF added as a raw material relative to the total weight of the above-mentioned lithium manganese-based oxide is 1,500 ppm), maintaining an O2 atmosphere in a sintering furnace, the temperature is raised to 400°C at a rate of 4.4°C / min, heat treated for 8 hours, classified and crushed to obtain a lithium manganese-based oxide with a fluorine-containing coating portion (including lithium fluoride) formed on the surface.

[0188] Example 1

[0189] After mixing the lithium manganese-based oxide and PVDF prepared in Comparative Example 1 (weighed so that the fluorine content based on the amount of PVDF added as a raw material relative to the total weight of the above-mentioned lithium manganese-based oxide is 1,500 ppm), maintaining an O2 atmosphere in a sintering furnace, the temperature was raised to 400°C at a rate of 4.4°C / min, heat treated for 8 hours, classified and crushed to obtain a lithium manganese-based oxide with a fluorine-containing (including lithium fluoride) coating formed on the surface.

[0190] Next, after mixing H3BO3 (weighed so that the boron content based on the amount of H3BO3 added as a raw material is 1,300 ppm relative to the total weight of the above-mentioned lithium manganese-based oxide), an O2 atmosphere is maintained in a sintering furnace, the temperature is raised to 400°C at a rate of 4.4°C / min, and heat treated for 8 hours, classified and crushed to obtain a lithium manganese-based oxide having a fluorine and boron coating portion (including lithium fluoride and lithium borate) formed on the surface.

[0191] Example 2

[0192] After mixing the lithium manganese-based oxide prepared in Comparative Example 1 and H3BO3 (weighed so that the boron content based on the amount of H3BO3 added as a raw material is 1,300 ppm relative to the total weight of the above-mentioned lithium manganese-based oxide), an O2 atmosphere is maintained in a sintering furnace, the temperature is raised to 400°C at a rate of 4.4°C / min, heat treated for 8 hours, classified and crushed to obtain a lithium manganese-based oxide having a boron-containing coating portion (including lithium borate) formed on the surface.

[0193] Next, after mixing PVDF (weighed so that the fluorine content based on the amount of PVDF added as a raw material relative to the total weight of the above-mentioned lithium manganese-based oxide is 1,500 ppm), maintaining an O2 atmosphere in a sintering furnace, the temperature is raised to 400°C at a rate of 4.4°C / min, heat treated for 8 hours, classified and crushed to obtain a lithium manganese-based oxide having a fluorine and boron coating portion (including lithium fluoride and lithium borate) formed on the surface.

[0194] Example 3

[0195] After mixing the lithium manganese-based oxide prepared in Comparative Example 1, PVDF (weighed so that the fluorine content based on the amount of PVDF added as a raw material is 1,500 ppm relative to the total weight of the above-mentioned lithium manganese-based oxide) and H3BO3 (weighed so that the boron content based on the amount of H3BO3 added as a raw material is 1,300 ppm relative to the total weight of the above-mentioned lithium manganese-based oxide), maintaining an O2 atmosphere in a sintering furnace, heating to 400°C at a rate of 4.4°C / min, heat treating for 8 hours, classifying and pulverizing, to obtain a lithium manganese-based oxide having a fluorine and boron coating portion (including lithium fluoride and lithium borate) formed on the surface.

[0196] Example 4

[0197] A positive electrode active material was prepared in the same manner as in Example 3 except that 150 ppm of PVDF and 3,300 ppm of H 3 BO 3 were used as the addition amount.

[0198] Example 5

[0199] A positive electrode active material was prepared in the same manner as in Example 3 except that 4,500 ppm of PVDF and 100 ppm of H 3 BO 3 were used as the addition amount.

[0200] Comparative Example 2

[0201] A positive electrode active material was prepared in the same manner as in Example 3 except that 50 ppm of PVDF and 3,300 ppm of H 3 BO 3 were used as the addition amount.

[0202] Comparative Example 3

[0203] A positive electrode active material was prepared in the same manner as in Example 3 except that 4,500 ppm of PVDF and 50 ppm of H 3 BO 3 were used as the addition amount.

[0204] Preparation Example 2. Fabrication of a lithium secondary battery (half-cell)

[0205] 90 wt % of each positive electrode active material prepared according to Preparation Example 1, 4.5 wt % of carbon black, and 5.5 wt % of PVDF binder were dispersed in N-methyl-2-pyrrolidone (NMP) to prepare a positive electrode slurry.

[0206] The positive electrode slurry was uniformly coated on an aluminum thin film with a thickness of 15 μm, and vacuum dried at 135° C., thereby preparing a positive electrode for a lithium secondary battery having a positive electrode active material layer formed thereon.

[0207] Relative to the above-mentioned positive electrode, lithium foil is used as a counter electrode, a porous polyethylene film (Celgard 2300, thickness: 25μm) is used as a separation membrane, and an electrolyte solution containing LiPF6 at a concentration of 1.15M in a solvent of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate mixed in a volume ratio of 2:4:4 is used to prepare a half-cell.

[0208] Preparation Example 3. Preparation of lithium secondary battery (full battery)

[0209] 90 wt % of each positive electrode active material prepared according to Preparation Example 1, 4.5 wt % of carbon black, and 5.5 wt % of PVDF binder were dispersed in N-methyl-2-pyrrolidone (NMP) to prepare a positive electrode slurry.

[0210] The positive electrode slurry was uniformly coated on an aluminum thin film with a thickness of 15 μm, and vacuum dried at 135° C., thereby preparing a positive electrode for a lithium secondary battery having a positive electrode active material layer formed thereon.

[0211] Relative to the above-mentioned positive electrode, a graphite electrode is used as a counter electrode, a porous polyethylene film (Celgard 2300, thickness: 25μm) is used as a separation membrane, and a full battery is prepared using an electrolyte solution in which LiPF6 is present at a concentration of 1.15M in a solvent of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate mixed in a volume ratio of 2:4:4.

[0212] Experimental Example 1. Analysis of coating composition

[0213] Each positive electrode active material prepared according to Preparation Example 1 was subjected to ICP-MS (Inductively Coupled Plasma-Mass Spectrometer) and CIC (Combustion Ion Chromatography) analysis to measure the contents of fluorine and boron in the positive electrode active materials according to Examples 1 to 5, Reference Examples 1 to 2, and Comparative Examples 1 to 3. The above measurement results are shown in Table 1 below.

[0214] Table 1

[0215] Classification fluorine boron Fluorine (ppm): Boron (ppm) unit ppm ppm - Example 1 1100 1300 1:1.2 Example 2 1100 1300 1:1.2 Example 3 1100 1300 1:1.2 Example 4 150 3000 1:25 Example 5 3500 100 1:0.03 Reference Example 1 0 1300 - Reference Example 2 1100 0 - Comparative Example 1 0 0 - Comparative Example 2 100< 2500 Unable to measure Comparative Example 3 3500 100< Unable to measure

[0216] Experimental Example 2. Evaluation of electrochemical performance of lithium secondary battery (half-cell)

[0217] The lithium secondary battery (half-cell) prepared according to Preparation Example 2 was subjected to a charge / discharge experiment using an electrochemical analyzer (Toyo, Toscat-3100) at 25°C, a voltage range of 2.0V to 4.6V, and a discharge rate of 0.1C to 2.0C to determine the initial charge capacity, initial discharge capacity, initial reversible efficiency, and rate performance (discharge capacity ratio; rate capability, C-rate). The above measurement results are shown in Table 3 below.

[0218] Table 2

[0219]

[0220] Referring to the results of Comparative Example 1, Reference Example 1 and Reference Example 2 in Table 2, it can be confirmed that when a fluorine-containing coating portion or a boron-containing coating portion is formed on the surface of the lithium manganese-based oxide, the initial capacity and initial efficiency are slightly improved.

[0221] On the other hand, when a coating portion in which fluorine and boron exist in a predetermined weight ratio is formed on the surface of the above-mentioned lithium manganese-based oxide, it can be confirmed that the initial capacity, initial efficiency and rate performance are significantly improved compared with Comparative Example 1.

[0222] Experimental Example 3. Evaluation of electrochemical performance of lithium secondary battery (full battery)

[0223] For the lithium secondary battery (full battery) prepared in Preparation Example 3, an electrochemical analyzer (Toyo, Toscat-3100) was used to complete 6 cycles of formation at 25°C, a voltage range of 2.0V to 4.6V, and 0.2C / 0.2C, and then charged / discharged 500 times at 25°C, a voltage range of 2.0V to 4.6V, and 1C / 1C. The initial (first cycle) discharge capacity and the ratio of the discharge capacity at the 500th cycle relative to the initial discharge capacity (cycle capacity retention; capacity retention) were measured.

[0224] The above measurement results are shown in Table 3 below.

[0225] Table 3

[0226]

[0227] Referring to the results in Table 3, it can be confirmed that the long-term life characteristics of the full battery using Comparative Example 1, in which no coating portion containing fluorine and / or boron is formed on the surface of the lithium manganese-based oxide, as the positive electrode active material rapidly decrease. It is estimated that the above result is because the transition metal dissolved from the lithium manganese-based oxide causes the resistance anomaly of the negative electrode, and the life deterioration of the full battery is accelerated due to the resistance anomaly.

[0228] Furthermore, it was confirmed that when a coating portion containing fluorine and boron at a predetermined weight ratio is formed on the surface of the lithium manganese-based oxide, long-term life characteristics are improved compared with the case where fluorine alone exists on the surface of the lithium manganese-based oxide.

[0229] Although the embodiments of the present invention are described above, those skilled in the art will understand that various modifications and changes can be made to the present invention by adding, modifying, deleting, increasing, etc., without departing from the scope of the idea of ​​the present invention as described in the claims, and these also fall within the scope of the rights of the present invention.

Claims

1. A positive electrode active material, characterized in that: include: Lithium manganese-based oxide, formed by solid solution of a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group; and A coating portion formed on at least a portion of the surface of the lithium manganese-based oxide; The coating portion contains fluorine and boron.

2. The positive electrode active material according to claim 1, characterized in that The fluorine may be present in an amount of greater than 100 ppm and less than or equal to 3,500 ppm based on the total weight of the positive electrode active material.

3. The positive electrode active material according to claim 1, characterized in that The coating portion includes LiF.

4. The positive electrode active material according to claim 1, characterized in that The lithium manganese-based oxide exists in the form of secondary particles formed by agglomeration of a plurality of primary particles. There is a gradient in which the fluorine concentration decreases from the surface portion toward the center portion of the secondary particle.

5. The positive electrode active material according to claim 1, characterized in that The coating portion further includes carbon.

6. The positive electrode active material according to claim 5, characterized in that The coating portion includes a carbonaceous matrix, and LiF is present in a dispersed state in the carbonaceous matrix.

7. The positive electrode active material according to claim 1, characterized in that The coating portion includes B2O3, H α B β O γ (0<α<10, 0<β<10, 0<γ<20) and Li α' B β' O γ' At least one boron-containing compound selected from the group consisting of (0<α'<10, 0<β'<10, 0<γ'<20).

8. The positive electrode active material according to claim 1, characterized in that The boron may be present in an amount of greater than 50 ppm and less than or equal to 3,000 ppm based on the total weight of the positive electrode active material.

9. The positive electrode active material according to claim 1, characterized in that The coating portion includes a single coating layer in which fluorine and boron coexist.

10. The positive electrode active material according to claim 1, characterized in that The coating section includes: (1) a first coating layer formed on at least a portion of the surface of the lithium manganese-based oxide and containing fluorine; and (2) A second coating layer formed on at least a portion of the surface of the first coating layer and containing boron.

11. The positive electrode active material according to claim 1, characterized in that The coating section includes: (1) a first coating layer formed on at least a portion of the surface of the lithium manganese-based oxide and containing boron; and (2) A second coating layer formed on at least a portion of the surface of the first coating layer and containing fluorine.

12. The positive electrode active material according to claim 1, characterized in that A weight ratio of the fluorine to the boron calculated based on the total weight of the positive electrode active material is 1:0.03 to 1:

25.

13. The positive electrode active material according to claim 1, characterized in that The average particle size of the lithium manganese-based oxide is 0.5 μm to 15 μm.

14. The positive electrode active material according to claim 1, characterized in that The lithium manganese-based oxide is represented by the following chemical formula 1: [Chemical formula 1] He(He a M1 x M2 y )O 2-b X b (in, M1 is at least one selected from Ni and Mn, M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd, and M2 and M1 do not repeat, X is a halogen that can replace at least a part of the oxygen present in the lithium manganese-based oxide, <a≤0.7、0≤b≤0.1、0<x≤1、0≤y<1、0<x+y≤1)。 15. The positive electrode active material according to claim 1, characterized in that The lithium manganese-based oxide is represented by the following chemical formula 1-1: [Chemical formula 1-1] rLi2MnO 3-c X' c ·(1-r)Li a' M1 x' M2 y' O 2-b' X b' (in, M1 is at least one selected from Ni and Mn, M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd, and M2 and M1 do not repeat, X and X' are each independently a halogen capable of replacing at least a portion of the oxygen present in the lithium manganese-based oxide, 0 <r≤0.7、0≤c≤0.1、0<a'≤1、0≤b'≤0.1、0<x'≤1、0≤y'<1、0<x'+y'≤1)。 16. A positive electrode, characterized in that: The positive electrode active material comprises the positive electrode active material according to any one of claims 1 to 15.

17. A lithium secondary battery, characterized in that: The present invention comprises the positive electrode as claimed in claim 16, a negative electrode, a separation membrane interposed between the positive electrode and the negative electrode, and an electrolyte.